The Effect of Practice on The Level of Performance of Some Basic Soccer Skills Among Young Women in Palestinian Clubs - Abutame, Bahjat Ahmad; Lahlooh, Sama; Baaziz, Mohamed; Aloui, Ali; Abderrahman, Abderraouf Ben (Advances in Social Sciences Research Journal, 2024)
The study aimed to identify the level of skillful performance of some basic soccer skills among young female players in Palestinian clubs, in addition to identifying differences in the level of performance according to the variable years of playing: 1-2 years, 3 years or more. To achieve this, the researchers used the descriptive approach, using and conducting skill tests (running with the ball, passing, controlling the ball, shooting, hitting the ball with the head), on a stratified random sample of (89) emerging female soccer players. The results of the study showed that the level of skillful performance of some basic soccer skills among female soccer players in Palestinian clubs was between average and good, in terms of the averages of the skill tests under study, as the average results of the ball running test was (17.01)/s, and the average passing skill was (11.6) times, controlling the ball had an average of (14.87) times, shooting skill with an average of (14.43) times, and hitting the ball with the head had an average of (4.04) times. The results of the study showed that there are no differences in the level of skillful performance among female soccer players depending on the variable years of playing, with the exception of the controlling the ball skill, for the benefit of three years or more. The researchers recommended the necessity of working to improve and develop the level of skill performance for basic skills among female soccer players in Palestinian clubs and this is through continuity of training.